2015
DOI: 10.1080/02699931.2015.1073692
|View full text |Cite
|
Sign up to set email alerts
|

Matching between oral inward–outward movements of object names and oral movements associated with denoted objects

Abstract: In eight experiments, we explored matching effects between oral approach-avoidance movements triggered by word articulation and meaning of the objects the words denoted. Participants (total N = 1264) rated their liking for words that featured consonantal muscle stricture spots either wandering inwards (e.g., BODIKA, resembling ingestion movements) or outwards (e.g., KODIBA, resembling expectoration movements). These words were labelled as names for various objects. For objects the use of which entails ingestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 59 publications
3
40
1
Order By: Relevance
“…As noted in the introduction of this manuscript, Topolinski et al. () found matching effects between articulation direction of object names and the oral actions associated with the objects, independently of the objects’ valence (e.g., inward words were preferred for ingestion‐related objects, such as lemonade or medicine, while outward words were preferred for objects associated with expectorative oral movements, such as toxic chemicals or bubble gum). It is an interesting empirical question whether these kind of matching effects would extend to sellers’ names and their perceived trustworthiness.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…As noted in the introduction of this manuscript, Topolinski et al. () found matching effects between articulation direction of object names and the oral actions associated with the objects, independently of the objects’ valence (e.g., inward words were preferred for ingestion‐related objects, such as lemonade or medicine, while outward words were preferred for objects associated with expectorative oral movements, such as toxic chemicals or bubble gum). It is an interesting empirical question whether these kind of matching effects would extend to sellers’ names and their perceived trustworthiness.…”
Section: Discussionmentioning
confidence: 77%
“…All this evidence clearly suggests that the experiences that accompany the reading of brand and seller names have a great potential to influence how consumers feel about them. In the next section, we will describe with more detail another name characteristic with the potential to influence judgments about brands, products, and people, and this is the target of the present research: the sequence of muscle movements that are involved in the articulation of words (e.g., Lindau & Topolinski, ; Topolinski & Boecker , ; Topolinski, Boecker, Erle, Bakhtiari, & Pecher, 7; Topolinski, Maschmann, Pecher, & Winkielman, ; Topolinski, Zürn, & Schneider, ; for a review, see Topolinski, ).…”
Section: Brand Product and Seller Name Effects On Consumer Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in follow‐up studies, this effect was generalized to consumer attitudes, where participants reported higher purchase likelihood and willingness‐to‐pay for products with inward than for products with outward brands (Topolinski, Zürn, & Schneider, 2015). Also, in a recent paper, the interaction of this articulation effect with word meaning was explored (Topolinski, Boecker, Bakthiari, & Pecher, in press). There, it was found that the in‐out effect is reduced or even reversed when these words denote objects that are associated with a strong expectorative oral action (e.g., bubble gums or toxical chemicals).…”
mentioning
confidence: 99%